Comparison of Immunomagnetic Separation and Multiplex PCR Assay for Detection of Campylobacter jejuni and Campylobacter coli in Chicken Meat - Chalermkiat Saengthongpinit,; Aldert A. Bergwerff,; Frans van Knapen,; Patamaporn Amavisit,; Theerapol Sirinarumitr,; Thavajchai Sakpuaram, (Agriculture and Natural Resources, 2007)
Campylobacter is one of the most common food-borne pathogens in the developed and developing countries. Poultry and poultry products are important vehicles for this bacterium to infect humans. Due to only a short time required for analysis of food products, more rapid, sensitive and specific methods have been developed for Campylobacter detection. Two alternative methods, multiplex PCR (mPCR) and immunomagnetic separation (IMS) followed by plating to charcoal cefoperazonedeoxycholate agar (CCDA), were compared for their suitability to detect Campylobacter jejuni and C. coli in chicken meat. IMS followed by plating could detect C. jejuni and C. coli inoculated at 100 cfu/g in meat after 12 h of incubation. The mPCR method could detect both species at the same inoculation level after 16 h of incubation. However, the total analytical time to identify C. jejuni and C. coli in chicken meat using IMS followed by plating was 72-96 h while the time used by mPCR was only 22 h. A single cell of C. jejuni or C. coli in 1 g of chicken meat was detected by mPCR after 16 h of incubation in Preston broth.